PEMBINAAN KEMANDIRIAN DAN PEMBINAAN AKHLAK ANAK DI GRIYA ADAB DAN QUR’AN AL KAUTSAR KOTA MADIUN - Qurrota A’yun, Neny; Dwi Nurcahyaningtias, Novia; Irfatul; Rohani, Imam (Institut Agama Islam Riyadlotul Mujahidin, 2024)
Parenting styles in educating children have a very important role in the process of forming a child's personality. The child's independence to carry out daily activities or work which is carried out personally with a little coaching or mentoring from someone as an educator/parent that is adapted to the stage of development and abilities at his age. It is very urgent for the formation of morals to be instilled in a child from an early age so that the good actions or manners taught can be used to apply them in their daily life. The aim of this research is to provide guidance and direction regarding independence and instilling morals in children. This research uses a descriptive method with a qualitative approach. Collecting data and information in service using observation, interviews and documentation studies. The results of the research show that there are 4 programs implemented in fostering independence and moral development in children. The existence of this program familiarizes children with carrying out their daily activities independently based on instilling good morals towards parents and others.